Workshop Control System Engineering melalui Kuliah Pakar dan Praktik Teknis untuk Mendukung Kompetensi Otomasi Industri Mahasiswa Vokasi - Jonathan Widodo Wiji Saputra; Mochammad Dimas Purwanto; Femy Nurmala Sari; Karina Puspita Sembada; Ahmad Almubarok Azimatul Islamiyah; Jovita Nina Rasyida; Wisnu Aditya Wardhana; Verina Bernice Waranggani; Septian Nugroho Wicaksono; Muhammad Faizullah; Sabillah Isnaini Ashar; Achmad Hamdan (JURPIKAT, 2026)
The development of industrial automation requires vocational students to have relevant competencies in control systems, robotics, and applied electronic technology. This community service activity aimed to support vocational students’ industrial automation competencies through a Control System Engineering workshop that combined expert lectures and technical practice. The activity was conducted over two days at the Faculty of Vocational Studies, Universitas Negeri Malang, involving 32 students. The first day focused on material delivery, discussion, and conceptual reinforcement of control systems, while the second day emphasized technical practice, device demonstrations, and robotics project consultation. Evaluation was conducted through observation, documentation, and participant response questionnaires. The evaluation results showed a very good response, with an overall mean score of 4.46. This activity contributed to supporting participants’ understanding of control systems, robotics applications, and the need for sustainable industrial automation project development.